Upaya Persuasi Lembaga Knowledge Management PT.Pusri Dalam Memotivasi Departemen-Departemen untuk Melakukan Sharing Knowledge - Rahman Akbar; Ahmad Muhaimin (Jurnal Prodi Ilmu Komunikasi, 2022)
In improving an employee's performance within the Work Units and Organizations under the auspices of the Department, it is necessary to carry out a knowledge that becomes an important guideline for employees at work. So that the creation of a Knowledge Worker is to work with the knowledge possessed. This study aims to describe how the efforts of the Knowledge Management institution or section in overcoming problems that occur within the company to share knowledge and the implementation of what is done from these persuasion efforts so that they can successfully motivate every Department in PT. Pusri to be interested in the existence of persuasion efforts carried out by Knowledge Management institutions. The method used in this research is descriptive qualitative observation and interviews by observing the atmosphere of the area around the offices of the Knowledge Management institution. From the results and discussion, it was found that there were two persuasion efforts carried out by Knowledge Management in motivating the Departments to share knowledge, firstly optimizing the persuasive communication program through the LEAP program, the second delivering interesting messages through animated videos and flayers.